(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: Eentrepreneurships helps women to become self-sufficient and economically independent, then it is the best way to empower them. Increased entrepreneurship has the capability to empower females politically, socially, and financially. The path of women’s empowerment has given them more power over resources. It is important not just for personal growth but also for the nation’s overall development. Objective: There are two objectives of the study: to study the elements responsible for women to run their business and to examine the challenges struggled by women entrepreneurs in managing their business. Methodology: Quantitative research was done. The data was collected from Lucknow city of Uttar Pradesh state. Convenience sampling was done and 200 respondents were reached for data collection and 195 responses were finalised. A structured questionnaire was made for research and was spread to respondents through Google forms and by personal interview. Mean value and reliability test were used to analyse the data. Results: The Cronbach’s static value was found 0.975 which is acceptable for the study. The weighted mean score it has been found that aspire to be independent ranked 1st (weighted mean score 2.8). Women requires financial need to run the business ranked 2nd (weighted mean score 2.7). Confirmation of family and career security are two important pillar to boost confidence in oneself ranked 3rd (weighted mean score 2.3). Women faced challenges for building infrastructure for their business ranked 1st (weighted mean score 3.5). Budgetary restrictions was the major issue for women entrepreneurs ranked 2nd (weighted mean score 3.4). Low mobility was third largest issue for the entrepreneurs ranked 3rd (weighted mean score 3.3). Conclusion: The study concludes that if women focus on the challenges faced by them in running business, they can overcome the issues. Proper training is always required of the concerned business and majorly help from Government and NGO’s can change the status of the women.